MK-927: a topically effective carbonic anhydrase inhibitor in patients - Bron, A M; Lippa, E A; Hofmann, H M; Feicht, B I; Royer, J G; Brunner-Ferber, F L; Panebianco, D L; Von Denffer, H A (Archives of ophthalmology (1960), 1989)
The effects on intraocular pressure of the novel topical carbonic anhydrase inhibitor MK-927 were investigated for the first time in patients. Three drops of 2% MK-927 was administered in a two-center, double-masked, randomized, placebo-controlled, two-period crossover study in 25 patients with bilateral primary open angle glaucoma or ocular hypertension. At 4.5 hours after the dose, MK-927-treated eyes demonstrated a peak mean change of -7.7 mm Hg from a mean intraocular pressure of 27.8 mm Hg immediately before the dose; this compares with a change of -3.9 mm Hg from a mean intraocular pressure of 28.2 mm Hg when the same eyes were treated with placebo. The peak mean percent change in intraocular pressure in eyes treated with MK-927 was -26.7% at 6 hours after the dose compared with a change of -13.7% after treatment with placebo. No contralateral effect on intraocular pressure due to MK-927 was observed.